Kant’s Aesthetic Theory: key issues. An Introduction by the Guest Editor of the Special Issue - Lemos, João (Con-Textos Kantianos. International Journal of Philosophy, 2020)
This introduction presents an overview of the special issue of Con-Textos Kantianos devoted to Kant’s aesthetic theory. The articles in this issue have been organized into two sections: those written by keynote-authors, and those written in response to the general call for papers. Within each of these two sections, articles have been organized thematically, although the philosophical traditions that they engage with, as well as points of contact between articles, have also been considered. In the first section, keynote-authors address questions of aesthetic normativity; the role of aesthetics in the acquisition of empirical concepts; the emotional nature of aesthetics; subjectivity and disinterestedness; connections between aesthetics, anthropology, and politics; and aesthetic non-conceptualism. The second section begins with contributions dealing with matters of formalism and conceptualism in Kant’s aesthetics, as well as their relation and relevance to thinking about art, the arts, and contemporary art. It continues with papers that address key issues of Kant’s aesthetics, such as the free play and the role of imagination, as well as possible complementarities between the three Critiques. It closes with articles that focus on the reception of Kant’s aesthetic theory in the works of major philosophers of the 20th century, namely within critical theory and the phenomenological-hermeneutical tradition.